Gender equality in earnings at work and at home - Annemette Sørensen (Luxembourg Income Study (LIS), 2001)
This paper examines how far Denmark, Finland, Norway and Sweden have achieved gender equality in earnings. These Nordic countries are contrasted with Germany, the Netherlands and the United Kingdom in the mid-1990s, and include some comparisons to the situation in the 1980s. While all these countries have experienced the same general changes in women's roles and positions, when these began and how fast they have progressed vary greatly. There is every reason to expect substantial country differences a the end of the 20th century, and that the four Nordic countries as a group have moved closer to realizing the political goals of gender equality in the labor market and a lessening of women's economic independence on men. There are three parts to the empirical analysis. The first is an examination of the gender differences in earnings for adults aged between 18 and 60. The second part concerns women's economic dependence on the men they live with and how much having small children increases that dependence. The third part of the analysis takes up the question of how more equality between spouses affects their dependence on each other and the inequality of economic risks.
Keywords: 330; Fraueneinkommen; Lohn; Geschlecht; Nordeuropa; Deutschland; Niederlande; Großbritannien